2015
DOI: 10.1242/jeb.120329
|View full text |Cite
|
Sign up to set email alerts
|

Memory block: A consequence of conflict resolution

Abstract: Food deprivation for 1 day in the pond snail Lymnaea stagnalis before aversive classical conditioning results in optimal conditioned taste aversion (CTA) and long-term memory (LTM) formation, whereas 5-day food deprivation before training does not. We hypothesize that snails do in fact learn and form LTM when trained after prolonged food deprivation, but that severe food deprivation blocks their ability to express memory. We trained 5-day food-deprived snails under various conditions, and found that memory was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 37 publications
(41 reference statements)
3
32
0
Order By: Relevance
“…Feeding suppressed appetitive memory, as it was shown by studies in Drosophila (29), but more interesting was that expression of aversive memory was enhanced in satiated crabs. This result is consistent with recent findings in crayfish showing that feeding modulates risk avoidance behaviors (36) and with studies in Lymnaea showing that hungry animals suppress the expression of taste aversion memory (37). We interpret the results in crabs as the consequence of an evaluation that the animal does in relation to costs, benefits and risks that it is willing to take.…”
Section: Mutual Interference Between Appetitive and Aversive Memoriessupporting
confidence: 92%
“…Feeding suppressed appetitive memory, as it was shown by studies in Drosophila (29), but more interesting was that expression of aversive memory was enhanced in satiated crabs. This result is consistent with recent findings in crayfish showing that feeding modulates risk avoidance behaviors (36) and with studies in Lymnaea showing that hungry animals suppress the expression of taste aversion memory (37). We interpret the results in crabs as the consequence of an evaluation that the animal does in relation to costs, benefits and risks that it is willing to take.…”
Section: Mutual Interference Between Appetitive and Aversive Memoriessupporting
confidence: 92%
“…That is, there is a conflict between the CTA memory and the desire/necessity to eat. As described in an earlier report (Ito et al, 2015b), the ‘necessity knows no law’ concept prevails in these snails. That is, snails do not express the memory phenotype if they are extremely hungry (for example, Day 5 snails), i.e.…”
Section: Discussionmentioning
confidence: 70%
“…This could be shown because the memory is context-dependent (Haney and Lukowiak, 2001; Lukowiak et al, 2007) and can only be observed when the snails are in a context similar to that in which the training occurred. Thus, if the Day 5 snails are fed after they received the training, the memory phenotype can be expressed (Ito et al, 2015b). Recently, dopamine was also shown to be involved in positive emotion states, even in invertebrates (Perry et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the Yerkes and Dodson (1908) paper did not present such an inverted-U curve. The inverted-U function is actually a figure adapted from Donald Hebb's 1955 presidential address to the American Psychological Association (Hebb, 1955; see also Diamond et al, 2007;Ito et al, 2015a;Kojima et al, 2015). It appears that Hebb was unaware of the earlier Yerkes and Dodson paper (Diamond et al, 2007).…”
Section: Discussionmentioning
confidence: 99%